2022
DOI: 10.1002/anie.202202200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Main‐Group Antimony Atomic Sites for Oxygen Reduction Catalysis

Abstract: The catalytic activity of main-group metal is hard to promote because of the intrinsic lack of host d orbitals available to be combined. Herein, under the guidance of theoretical predictions, we find atomdispersed antimony sites (SbÀ N 4 moieties) can be activated to achieve high oxygen reduction reaction (ORR) activity using a functional group regulation strategy. Correspondingly, we manage to synthesize a main-group Sb single-atom catalysts (SACs) that comprises SbÀ N 4 active moieties functionalized by epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…Based on the above analyses, it can be concluded that the nearby OFGs can further adjust the binding strength of OOH* over Co−N 4 sites toward more favorable 2 e − ‐ORR energetics [12d, 40] . According to previous reports, the carbon sites at the oxygen‐terminated edges could be activated as additional binding sites to promote the electrochemical synthesis of H 2 O 2 via 2 e − ‐ORR process [22a, 38a] .…”
Section: Resultsmentioning
confidence: 76%
“…Based on the above analyses, it can be concluded that the nearby OFGs can further adjust the binding strength of OOH* over Co−N 4 sites toward more favorable 2 e − ‐ORR energetics [12d, 40] . According to previous reports, the carbon sites at the oxygen‐terminated edges could be activated as additional binding sites to promote the electrochemical synthesis of H 2 O 2 via 2 e − ‐ORR process [22a, 38a] .…”
Section: Resultsmentioning
confidence: 76%
“…In contrast, main group metals including s-and p-block elements are thought to be catalytic inactive due to the delocalized s/p-band, and have rarely been explored in the area of SACs. [90,91] Some most recent efforts have demonstrated that main-group element SACs (e.g., Mg, Sn, Sb, Bi, Se, Te) can be activated by fine regulation of the local coordination environments and will be attractive to steer the reaction pathways for ORR, [90][91][92][93][94] CRR, [95][96][97] and NRR. [98] For example, the Mg SACs coordinated with two nitrogen atoms in graphene was revealed to weaken the binding strength of oxygenated species compared to larger coordination numbers, rendering near-optimal adsorption strength and outstanding ORR activity in alkaline media.…”
Section: Molecular-level Single-atom Catalystsmentioning
confidence: 99%
“…The significant role of epoxy groups in the second CS on resulting ORR activity or selectivity was also confirmed in other Co SACs and Sb SACs. [ 92,106,107 ] Analogously, S heteroatoms in the second CS of Ru SACs was revealed to induce indirect electronic regulation of the center Ru atom, evidenced by X‐ray photoelectron spectroscopy (XPS) and extended X‐ray absorption fine structure (EXAFS) analysis. [ 108 ] Compared with the routine RuN 4 C moiety, the anion‐coordinated RuN 4 SC sites exhibited weakened adsorption of intermediates, leading to higher ORR activity and long‐term stability.…”
Section: Emerging Graphene Derivatives For Efficient Electrocatalysismentioning
confidence: 99%
“…The ORR is essential for the application of Zn-air batteries, and Pt-based catalysts are usually deemed to be the most effective materials for catalyzing the ORR. [1][2][3][4][5][6] But the high price and weak stability of Pt-based catalysts have been decisive factors in their large-scale application. [7][8][9] Therefore, it is imperative to study Ptfree catalysts to replace Pt-based catalysts.…”
Section: Introductionmentioning
confidence: 99%